PENYANDIAN DATA TEKS MENGGUNAKAN ALGORITMA CIPHER FEED-BACK DAN CHAOTIC SKEW TENT MAP - Anita M Sonbay; Adriana Fanggidae; Kornelis Letelay (J-Icon : Jurnal Komputer dan Informatika, 2017)
Security for documents that contain confidential text and important for a company, institution, or organization from disorders irresponsible organisation is a necessity or a major requirement that must be done, so we need a software that can protect these vital documents. The combination of algorithms Chiper Feed-back (CFB), Chaos Skew Tent Map (CSTM), and the initial value generation techniques with Session Keys capable of encrypting the text properly. Tests conducted on 26 files doc, docx and txt where each test will be analyzed the correlation, standard deviation and variance, as well as the histogram. Testing is done to the file doc, docx, and txt with a size ≤ 35 kb, 30-60 kb, 61-80 kb and > 80 kb. The test results obtained by the value of the average correlation = 0.163326411, standard deviation = 1.068,070, variance = 1.550.358,492, and the ciphertext histogram that visually looks uniform, making it difficult to analyze the statistical analysis of the character or key.